Stabilizing rational speculation and price level targeting - Franco Reither; Lars Bennöhr (Helmut-Schmidt-Universität - Universität der Bundeswehr Hamburg, Fächergruppe Volkswirtschaftslehre, 2010)
We analyze the contribution of speculation to exchange rate volatility using different assumptions regarding speculation strategies and monetary policy rules. We take the DORNBUSCH (1976) model as the starting point and adopt a slight modification of the money demand specification. With a money supply rule, rational speculation dampens the overshooting of the exchange rate following a money supply shock, compared with speculation based on static expectations. Then, we replace the LM condition by a TAYLORtype price level targeting rule rule. The resulting 'DORNBUSCH-TAYLOR' model generates a unique saddle point solution even under 'strict' inflation targeting, if speculation is based on rational expectations. Under 'flexible' inflation targeting, exchange rate overshooting induced by a monetary policy shock is less pronounced under rational speculation than under static speculation. FOREX market equilibrium doesn't exist at all if speculation is static and monetary policy adopts'strict' inflation targeting.
urn:nbn:de:gbv:705-opus-26293
Keywords: E44; F31; F41; 330; Fair rational expectations; DORNBUSCH Model; open economy macroeconomics; speculation; FOREX; Wechselkurs; Overshooting; Devisenspekulation; Rationale Erwartung; Monetäre Wechselkurstheorie; Geldangebot; Schock; Inflation Targeting; Devisenmarkt; Gleichgewicht; Theorie